An Ontological Model and Services for Capturing and Tracking Provenance in Decentralized Social Networks - Souza, Cíntia; Ronaldo Júnior, José; Prazeres, Cássio (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2021)
The rise of Decentralized Online Social Networks (DOSNs) and the increase in the number of active users on these networks offer an opportunity to develop solutions related to verifying origin, description paths and indicating the trajectory of the data that traffic in these networks. Provenance information is a key aspect of social networks because it is possible to evaluate the authenticity, reliability, and relevance of the information through its results. The speed of information generation and sharing, the decentralized storage strategy associated with the large volume of data represents a challenge for data provenance. Thus, this paper proposes DOSNPROV, a data provenance ontological model based on the W3C PROV-O specification. In addition, this paper proposes services based on DOSN-PROV model to support capture and tracking of provenance information in DOSNs. We evaluated DOSN-PROV model in two stages and demonstrated its quality and compliance with the proposed domain. The services underwent an evaluation of their performance and their results indicated acceptable response times.